Finding positive SARS-CoV-2 RT-PCR in cerebrospinal fluid of two pediatric patients with severe COVID-19: a brief case report - Reza Sinaei; Habibeh Nejadbiglari; Roya Sinaei; Maziar Zeinaly; Sara Pezeshki; Maedeh Jafari (BMC, 2023)
Abstract Background There is growing evidence of nervous system involvement and related complaints in children with coronavirus disease 2019 (COVID-19). However, it seems that attempts to track of the virus in the nervous system have so far been unsuccessful. Case presentation Here we describe two pediatric cases of severe COVID-19 who had positive cerebrospinal fluid (CSF) and nasopharyngeal polymerase chain reaction (PCR) tests for severe acute respiratory syndrome coronavirus disease 2019 (SARS-CoV-2). A 36-month-old girl who presented with fever, diarrhea, mild left ventricular dysfunction and bizarre movements, and a five-month-old boy who presented with fever, watery diarrhea, severe dehydration, mottling, and two episodes of seizure. Their CSF analyses and cultures were normal. They admitted in intensive care unit (ICU) for near four days and discharged after ten days without any complaint. Conclusion This is one of the first reports of the presence of coronavirus in the central nervous system in COVID-19 pediatric patients, emphasizing the neurotropism and neuroinvasion characteristics of the virus.